Artesunate Suppresses the Proliferation and Development of Estrogen Receptor-α-Positive Endometrial Cancer in HAND2-Dependent Pathway - Yin, Xianghua; Liu, Yan; Qin, Jiarui; Wu, Yixuan; Huang, Jiayan; Zhao, Qi; Dang, Tingting; Tian, Yacui; Yu, Ping; Huang, Xiyue (Frontiers in Cell and Developmental Biology, 2021)
Endometrial carcinoma (EC) is a common leading cause of cancer-related death in women, which is associated with the increased level of estrogen in the body. Artesunate (ART), an active compound derived from Artemisia annua L., exerted antitumor properties in several cancer types. However, the role of artesunate and the molecular basis on EC remains unclear. Here, we aimed to explore the effects and mechanisms of artesunate. Our results identified that estrogen receptor-α (ER-α) was a key factor for the type I EC (ER-α-positive), which might suppress the downstream LKB1/AMPK/mTOR pathway. Besides, we found ART significantly inhibited tumor proliferation in a dose-dependent manner. Mechanistic studies identified that ART led to tumor cell apoptosis and cell cycle arrest by downregulating the ER-α expression and activating the LKB1/AMPK/mTOR pathway. In addition, we found ART could increase the expression of HAND2 in the ER-α-positive EC cells, which could interact with ER-α. Through the gain-and loss-function experiments, we showed that over expression of HAND2 repressed the proliferation and migration of ER-α-positive EC cells via inhibition of ER-α expression. HAND2 knockdown increased ER-α expression and alleviated the antitumor effect of ART in vitro and in vivo. Overall, our study first showed that ART could be an effective antitumor agent through modulating ER-α-mediated LKB1/AMPK/mTOR pathway in the HAND2 dependent manner. Our findings provide an effective therapeutic agent for ER-α-positive EC treatment.